The failure mechanism of surrounding rock around an existing shield tunnel induced by an adjacent excavation. (January 2020) - Huang, Fu; Zhang, Min; Wang, Fen; Ling, Tonghua; Yang, Xiaoli
Abstract: Foundation pit excavation may disturb the initial stress field and induce the deformation of the surrounding rock mass. Due to the excavation, the originally compact rock mass and lining structure may become loose with adverse impacts on the normal operation of the existing tunnel. A new failure mechanism is constructed on the basis of the deformation characteristics of the rock mass around an existing tunnel induced by an adjacent excavation. Using this failure mechanism, the upper bound solution of the slip surface equation for the rock mass around an existing tunnel is derived in the framework of the upper bound theorem in conjunction with a variational approach. The shape and range of the slip surface are plotted for different parameters. A three-dimensional numerical model is constructed to simulate the deformation of the rock mass around the existing tunnel induced by adjacent excavation. By comparing the analytical results for the slip surface with the failure surface provided by numerical simulation, it is found that the differences between the analytical results and the numerical results are small. This comparison shows that the proposed method is valid for investigating the deformation of the rock mass around the existing tunnel induced by adjacent excavation.